2016
DOI: 10.4314/jasem.v19i4.22
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Mn(II) and Co(II) ions from aqueous solution using Maize cob activated carbon: Kinetics and Thermodynamics Studies

Abstract: ABSTRACT:The adsorption of Mn(II) and Co(II) ions from aqueous solution was investigated using batch adsorption experiment at room temperature. The effect of pH, contact time, metal ion concentration and temperature were evaluated. The residual concentrations of the metal ions were determined by atomic absorption spectrophotometer. The results showed that maximum removal of Mn(II) and Co(II) ions occurred at pH 9. Some physico-chemical and spectroscopic characterization of the adsorbents were done such as mois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…It has been reported that adsorbents with high iodine number/surface area perform better in the removal of small-sized contaminants. 22 The point of zero charge (pH ZPC ) of AMP was obtained at 7.2. This implies that the prepared carbon is free from surface charges near neutral pH.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that adsorbents with high iodine number/surface area perform better in the removal of small-sized contaminants. 22 The point of zero charge (pH ZPC ) of AMP was obtained at 7.2. This implies that the prepared carbon is free from surface charges near neutral pH.…”
Section: Resultsmentioning
confidence: 99%
“…Carbonization Process: A known amount of coconut coirpith was carbonized in a muffle furnace for 1 hour at 500 o C, to convert the raw material to carbon, burn off volatile organic matter and also to increase its surface area, after which it was allowed to cool, then, weighed (Adebayo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…It was later cooled in a water bath then filtered. It was then washed to neutrality with deionized water (to remove the residual acid) and dried at 105 o C in an oven (Adebayo et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Freundlich the exponent (n), known as heterogeneity factor, is in range of 1.566-2.754, which falls within the ranges of 1 to 10 and this indicates favourability of the adsorption as well as advantageous adsorption [70]. Value of 'n' tending towards 10 displays a higher degree of homogeneity of the particle surface [71].…”
Section: Against Timementioning
confidence: 99%